Menakar Ulang Diskursus Menstruasi: Kajian atas Aturan Puasa bagi Perempuan Haid dalam Fikih sebagai Upaya Menghapus Stereotype dan Menstrual Taboo - Wardah Nuroniyah (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2022)
The issue of menstruation has attracted a lot of attention from fiqh scholars to discuss it, because the scholars have tried to eradicate and abolish the myths surrounding menstruation that have existed for a long time. But if we want to take a closer look at the stipulations, more or less there are still stereotypes in treating menstruating women, although there are still debates in it. The explanation in fiqh still causes ambiguity in the argument why menstruating women are prohibited from fasting, is there still a misogynistic assumption about menstruation in fiqh, so that menstruating women are not allowed to fast? From this point of view, it is necessary to re-examine why menstruating women are prohibited from fasting, because the scholars of fiqh do not provide sufficient studies on various implications arising from the existence of the menstrual cycle, except for a global explanation of all the prohibitions that must be avoided for women menstruating. In the book of fiqh it is explained that fasting is forbidden for menstruating women because fasting is pure worship. This study concludes that by looking at the physical conditions experienced by menstruating women in general, the prohibition of menstruating women from fasting can be understood as people who are sick who get relief to break their fast for the benefit of and maintain their health. So the prohibition of a menstruating woman from fasting is a relief (rukhsah) from God to maintain the stability of her body, and it does not mean a prohibition, considering that the condition of a menstruating woman's body is not the same.